A Case of Metastatic Malignancy Presenting as Diffuse Alveolar Hemorrhage, a Diagnostic and Management Challenge! - Saira Jafri, Faizan Hussain, Zafar Ahmed, Muhammad Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Life-threatening hemoptysis (LTH) is one of the most dreaded respiratory emergencies. If not managed timely, results in inevitable mortality. Methodology: Documented the case and all the relevant details from the ICU of Liaquat National Hospital, Karachi. Case: We present a case that was unusual because a young male with no previous comorbidities, and a non-significant exposure history, presented with diffuse alveolar hemorrhage (DAH) and life-threatening hemoptysis. He had come with an extremely short presentation and was diagnosed as metastatic carcinoma, of unknown origin after his demise unfortunately even after expanding all possible avenues and approaching via multidisciplinary teams. If more of such cases are reported and documented, an etiology of DAH and LTH as secondary to malignancy can be more established. Conclusion: While dealing with cases of LTH, a malignancy focus must also be sought. The significance of detailed clinical examination is high. Keywords: Diffuse alveolar hemorrhage, life-threatening hemoptysis, massive hemoptysis, metastatic malignancy